Georg Friedrich Haas and Rebecca Saunders premieres, Huddersfield Contemporary Music Festival 2016. - Jones, Stephanie (Tempo, 2017)
The first weekend of the 2016 Huddersfield Contemporary Music Festival saw an eclectic and vibrant mix of musical events. Artistic director Graham McKenzie promised a festival that was going to be ‘undoubtedly characterised by the bringing together of often quite disparate forces, to create new sounds, new experiences, and new approaches to music making’, and the opening days also manifested a strong sense of artistic difference and distance as well. The presence of Georg Friedrich Haas, this year's Composer in Residence, and Rebecca Saunders seemed to fire up such underlying dynamic energies. Throughout the weekend both composers took part in public interviews and both had UK and world premieres, yet they only presented in parallel: the programming kept them apart. In turn, the weekend amplified various levels of similarity and divergence between the two composers, exposing some fascinating creative tensions.